Daily Fermented Whey Consumption Alters the Fecal Short-Chain Fatty Acid Profile in Healthy Adults - Smith, Nicola M.; Maloney, Niamh G.; Shaw, Sophie; Horgan, Graham W.; Fyfe, Claire; Martin, Jennifer C.; Suter, Andy; Scott, Karen P.; Johnstone, Alexandra M. (Frontiers in Nutrition, 2020)
Gut microbiota influences many aspects of host health including immune, metabolic and gut health. We examined the effect of a fermented whey concentrate (FWC) drink rich in L-(+)-Lactic acid, consumed daily, in 18 healthy men (n=5) and women (n=13) in free-living conditions. Objective: The aims of this 6-week pilot trial were to (i) identify changes in the gut microbiota composition and faecal short chain fatty acid (SCFA) profile, and (ii) to monitor changes in glucose homeostasis. Results: Total faecal SCFA (mM) concentration remained constant throughout the intervention. Proportionally, there was a significant change in the composition of different SCFAs compared to baseline. Acetate levels were significantly reduced (-6.5%; p<0.01), coupled to a significant increase in the relative amounts of propionate (+2.2%; p<0.01) and butyrate (+4.2%; p<0.01), respectively. No changes in the relative abundance of any specific bacteria were detected. No significant changes were observed in glucose homeostasis in response to an oral glucose tolerance test. Conclusion: Daily consumption of a fermented whey product led to significant changes in faecal SCFA metabolite profile, indicating some potential prebiotic activity. These changes did not result in any detectable differences in microbiota composition. Post-hoc analysis indicated that baseline microbiota composition might be indicative of participants likely to see changes in SCFA levels. However, due to the lack of a control group these findings would need to be verified in a rigorously controlled trial. Future work is also required to identify the biological mechanisms underlying the observed changes in microbiota activity and to explore if these processes can be harnessed to favourably impact host health.